Get Set for Success : Using Online Self-Assessments to Motivate First Year Engineering Students to Engage in and Manage Their Learning : Final Report. - Burton, Lorelle; Dowling, David; Albion, Majella (Office for Learning and Teaching, 2014)
Final report from the Get Set for Success project which aimed to address the looming skills shortage in the Australian engineering profession by better identifying the key factors underpinning student success in transitioning to engineering studies. Members of the project team came from five universities that cover the spectrum of Australian universities and engineering programs. The team compared and contrasted student self-assessment data against academic performance, using both quantitative and qualitative research methods. The key findings were that while mathematics and other relevant subject-related cognitive skills were the most important predictors of academic success, non- technical skills such as approaches to learning, interest and motivation in studying engineering, were also significant. Data from the 2012 and 2013 studies informed the development of an online engineering career appraisal tool (EngCAT) for students considering a career in engineering. The EngCAT website can be used for careers advice - it includes information and resources to help prospective students better understand their individual learning approaches, how they work in teams, and whether they have the skills and interest to pursue a career in engineering. This enhanced self-awareness will enable prospective students to seek support where needed and better manage their learning to successfully progress through their engineering program. EngCAT is an online educational resource that enables prospective engineering students to self-test their interest and motivation in engineering and make an informed choice about their career path. The EngCAT website can be used for careers advice – helping prospective students better understand their individual learning approaches, how they work in teams, and whether they have the skills and interest to pursue a career in engineering. This enhanced self-awareness will enable students to seek support where needed and better manage their learning to successfully progress through their program. EngCAT is designed to help the engineering industry attract students who have the required skill sets but may not otherwise have considered a career in engineering